Dynamics and design of space nets for orbital capture - Yang, Leping; Zhang, Qingbin, 1964-; Zhen, Ming; Liu, Haitao (Springer, 2017)
This book covers the topics of theoretical principles, dynamics model and algorithm, mission analysis, system design and experimental studies of space nets system, aiming to provide an initial framework in this field and serve as a ready reference for those interested. Space nets system represents a forefront field in future development of aerospace technologies. However, it involves new challenges and problems such as nonlinear and distorted nets structure, complex rigid flexible coupling dynamics, orbital transfer of space flexible composite and dynamics control. Currently, no comprehensive books on space nets dynamics and design are available, so potential readers can get to know the working mechanism, dynamics elements, and mission design of the space nets system from a Chinese perspective.